Towards safely managed water for all: the nature of accessibility, quality and reliability of drinking water sources in the upper regions of Ghana - Dongzagla, Alfred (2019)
In recognition of the multiple dimensions of access to drinking water, this study explored in detail the nature of accessibility, quality and reliability of drinking water sources in the Upper Regions of Ghana to inform monitoring and the provision of ‘safely managed water’ for all. Methodologically, the study adopted a mixed-method research approach in order to build complementarity and synergy between quantitative and qualitative methods. Quantitative data were collected through a household survey with principal housekeepers and water quality testing of three priority contaminants, comprising of faecal matter, fluoride and arsenic. Qualitative data on the other hand were collected through focus group discussions with women, men, children and water committees, and in-depth interviews with key managers of water supply systems. Results from both quantitative and qualitative data were integrated to enrich the findings of the study. From the results, the nature of accessibility, quality and reliability of drinking water sources in the Upper Regions of Ghana leaves much to be desired. Only 1.9% of the population had access to water in their compound. About 48.6% of the population’s roundtrip water collection time exceeded the World Health Organization (WHO) recommended limit of 30 minutes for at least basic access. This proportion increased to 50.8% based on the Joint Monitoring Programme (JMP) indicator of at most 30 minutes roundtrip water collection time from an improved source. In terms of quality, only 58.5% of the population had access to safe drinking water. The remaining 41.5% drinking water was contaminated, mainly with faecal matter, and in a few cases fluoride. Risk of exposure to faecal matter in drinking water was significantly higher in the rainy season than in the dry season. Also, drinking water sources in the rainy season were more reliable than in the dry season with year round access being 74.3%. Access to ‘safely managed water’ was generally low with marginal differences between the rainy (0.1%) and dry (1.0%) seasons. Based on the findings, the study makes two main conclusions. Firstly, Ghana and other resource-poor countries risk missing target 6.1 of the Sustainable Development Goal unless there is increased commitment to the provision of drinking water supply. Secondly, the JMP risks overestimating access to ‘safely managed water’ if seasonality in faecal contamination of drinking water sources, seasonality in the reliability of drinking water sources and secondary water sources are not monitored.